2013
DOI: 10.1063/1.4804657
|View full text |Cite
|
Sign up to set email alerts
|

First-principles study of edge-modified armchair graphene nanoribbons

Abstract: We have used first-principles methods to study the geometries and electronic structures of hydrogen (H), fluorine (F), chlorine (Cl), and hydroxyl (OH) terminated armchair graphene nanoribbons (H-AGNRs, F-AGNRs, Cl-AGNRs, and OH-AGNRs) with ribbon widths N = 7 and 19. The most stable geometries of H-AGNRs have planar configurations, but those of F-, Cl-, and OH-AGNRs have rippled edges. The ripples stem from steric hindrances between neighboring pairs of terminal atoms or groups, and the ripples are strongly l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 30 publications
2
29
0
1
Order By: Relevance
“…Therefore, it is highly desirable to make graphene and GNRs functionalized. Jippo et al 10 used H, F, Cl, and OH to passivate AGNRs and found that the halogen elements and OH can lead to the narrowing of bandgaps greatly. Among them, edge modification is one of the most popular chemical methods, by which the electromagnetic properties are modulated significantly.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is highly desirable to make graphene and GNRs functionalized. Jippo et al 10 used H, F, Cl, and OH to passivate AGNRs and found that the halogen elements and OH can lead to the narrowing of bandgaps greatly. Among them, edge modification is one of the most popular chemical methods, by which the electromagnetic properties are modulated significantly.…”
Section: Introductionmentioning
confidence: 99%
“…The strain changes the electronic property of AGNRs from semiconducting to metallic. 36,37 We calculated the current densities for the model at two bias voltages of 0.5 V and 1.0 V using the NEGF method. The errors in the current densities are shown in Fig.…”
Section: B Accuracy Checks In the Transport Calculationsmentioning
confidence: 99%
“…The electronic structures of AGNRs are sensitive to the structural deformations. 36 Therefore, we here deform only the metal surfaces for the purpose of investigating the ideal transport properties of graphene itself depending on the contacting metals. The artificial lattice compression causes a slight change in the work function from 4.42 eV to 4.53 eV for the Ti(0001) surface and from 5.33 eV to 5.36 eV for the Au(111) surface, where the work function is evaluated as the difference between the Hartree potential in the vacuum and the Fermi energy by placing empty atoms on the metal surfaces.…”
Section: A Interfacesmentioning
confidence: 99%
“…In addition to the edge shapes, the electronic structure also substantially depends on the chemical functional groups attached to the edges. [15][16][17][18][19][20] Hydroxylation of the graphene edges renders the peculiar delocalized state to the graphene edge. The state crosses the Fermi level and provides an electron channel in the vacuum spacing alongside the graphene edges with the free electron nature.…”
Section: Introductionmentioning
confidence: 99%